The incidence and burden of injuries in elite English youth female soccer players - Beech, J.; Jones, B.; King, R.; Bennett, P.; Young, S.; Williams, S.; Stokes, K.; Emmonds, S. (Science and Medicine in Football, 2022)
This study aimed to investigate the incidence, severity and burden of injury in English elite youth female soccer players. Qualified therapists at six English girls` academies prospectively recorded all injuries that required medical attention or caused time loss for matches and training in 375 elite youth female soccer players (under-10 [U10], U12, U14 and U16) during the 2019/2020 season. One hundred- and eleven time-loss injuries (52 from training, 59 from matches) were sustained, resulting in 1,946days absent (779days from training injuries, 1,167days from match injuries) from soccer activities. The injury incidence for matches (9.3/1000hours, 95% CIs: 7.2-11.9) was significantly greater than training (1.1/1000hours, 95% CIs: 0.9-1.5, p <0.001). Additionally, the injury burden for matches (183days lost/1000hours, 95% CIs: 142-237) was significantly greater than training (17days lost/1000hours, 95% CIs: 13-22, p <0.001). Injury incidence and burden were greatest in the U16 age group and were found to increase with age. Whilst injury incidence and burden are greater in matches than training, a large proportion of preventable injuries, soft-tissue and non-contact in nature, were sustained in training. Findings provide comparative data for elite youth female soccer players.